Māori Patient Experiences of Hand Therapy in Tāmaki Makaurau - Sheehy, Becky (Auckland University of Technology, 2024)
In Aotearoa, Māori are more likely to sustain a life changing injury and are less likely than non-Māori to access physical rehabilitation. Hand therapy, a subdiscipline of physical rehabilitation, offers advice and treatment for conditions affecting the upper limb. Little is known about Māori service user experiences of physical rehabilitation, including hand therapy. This research aimed to investigate Māori patient experiences of hand therapy and to explore solutions proposed by Māori to enhance culturally safe delivery of hand therapy services. The research was underpinned by a Tiriti o Waitangi informed approach and was completed in two phases. Phase one was a scoping review of the literature that aimed to synthesise what is currently known about Māori experiences of physical rehabilitation in Aotearoa. Four themes were created from data found in published and grey literature. The themes provide a narrative that describes Māori expectations for negative health encounters. Negative experiences during rehabilitation can be mitigated by including whānau, recognising Te Ao Māori, and providing mana-enhancing care. The findings from the scoping review informed the interview guide for phase two of the research. Phase two was a qualitative study that aimed to explore Māori experiences of hand therapy in Tāmaki Makaurau and solutions for enhancing hand therapy services for Māori. Semi-structured, exploratory interviews were carried out with 15 Māori hand therapy patients. Five themes were generated using reflexive thematic analysis. The qualitative study findings demonstrated that the initial connection with a therapist and first impressions of a clinic impacted on the hand therapy rehabilitation journey. Hand therapy was described as a different type of health service that was easier and more enjoyable to engage with compared to acute and primary care services. The key feature that stood out for participants was the taonga of the relationship formed with their hand therapist. Solutions for improving the cultural safety of hand therapy services included genuine incorporation of Te Ao Māori to facilitate cultural connections and expanding services for the provision of holistic and wraparound care for Māori patients, whānau, and communities. This research found that there are pockets of individual clinicians demonstrating culturally safe practice. Hand therapists, and other rehabilitation professionals, hold a privileged position with Māori when a meaningful connection is formed leading to a therapeutic relationship that is held as a taonga. This treasured relationship opens opportunities for hand therapists to normalise positive health experiences for Māori, offer options to engage with Te Ao Māori during appointments, and provide care that shelters hauora Māori.